Copper complexes suppress stemness, reverse epithelial‐to‐mesenchymal transition progression, and induce apoptosis on triple negative breast cancer. (15th February 2023) - Li, Dongdong; Dai, Linlin; Wang, Luyao; Tan, Cheng; Cai, Jun; Wang, Hui; Zhao, Xiumei
Abstract : Cancer stem cells (CSCs) are a small proportion of tumor cells with great tumorigenicity, self‐renewal ability, and intrinsic resistance to conventional and targeted cancer therapy; thus, targeting CSC is becoming an emerging cancer treatment. In this paper, five novel copper (II) complexes [Cu(OH‐PIP)(Tyr)(H2 O)]PF6 (1 ), [Cu(m‐OH‐PIP)(Gly)]NO3 ·2.25H2 O (2 ), [Cu(Cl‐PIP)(Gly)Br] (3 ), [Cu(F‐PIP)(Tyr)Cl] (4 ), and [Cu(F‐PIP)(Phe)Br] (5 ) have been synthesized and characterized by infrared spectroscopy and single crystal X‐ray diffraction analysis. All the complexes were screened for their in vitro cytotoxicity activity against a panel of human breast cancer cells (CAL‐51, MDA‐MB‐231, and MCF‐7), human liver cancer cells (HepG 2, SMMC‐7721) and human pancreatic cancer cells (PANC‐1) using MTT assay. They have potential proliferative inhibition for all the tested cancer cell lines, especially the triple‐negative breast cancer (TNBC) CAL‐51 cells are inhibited significantly with IC50 values ranging from 0.11 to 2.35 μM. Cellular functional assays showed that representative complexes 1 and 5 could trigger apoptosis, evidenced by Hoechst 33258 staining, flow cytometry assays, and the alteration of Bax, Bcl‐2, Caspase‐3, and PARP levels. In addition, they dramatically suppressed colony and mammosphere formation, inhibited cancer cell stemness and migration, and reversed epithelial–mesenchymal transition (EMT) progression in CAL‐51 cells, indicating their great potential as anti‐CSC agents for therapy of TNBC. Abstract : Copper (II) complexes displayed obvious cytotoxicity against the triple‐negative breast cancer (TNBC) CAL‐51 cells with IC50 values ranging from 0.11 to 2.35 μM. The representative complexes 1 and 5 could trigger apoptosis, evidenced by Hoechst 33258 staining, flow cytometry assays, and the alteration of Bax, Bcl‐2, pro‐Caspase‐3, and pro‐PARP levels. They also dramatically suppressed colony and mammosphere formation, inhibited cancer cell stemness and migration, and reversed EMT progression, indicating their great potential as anti‐CSC agents for therapy of TNBC.